Principal managerial creativity to increase teacher performance and student outcome - Corry Yohana; Annisa Lutfia; Shaierah Gulabdin; Herlinawati; Iskandar Agung; Abdul Kadir Ahmad; Achmad Habibullah; Imran Siregar; Achmad Dudin; Hasbi Indra (Society of Cultural Studies and Social Sciences, Hong Kong, 2023)
This paper aims to discuss the influence of critical thinking, collaboration, school vision, emotional intelligence, and school environment on principals' managerial creativity variables, then their effect on teacher performance and student learning outcomes. This paper is the result of a study of 112 school principals at the public and private elementary school, junior high school, and high school levels. Data collection was carried out by distributing questionnaires as one of the Google Docs applications. The research analysis uses the SEM 8.70 program technique, especially to see the effect between variables and the contribution of indicators to each variable. This study found that the variables of critical thinking, collaboration, vision, emotional intelligence, and the school environment had a significant positive effect on the managerial creativity of school principals. Efforts to build the managerial creativity of school principals need to pay attention to the variables that influence these, and the indicators that have the strongest contribution to each of the variables described in this study.